Fixed Points for \((α,β)\)-Admissible Mappings via Simulation Functions - Dewangan, Archana; Dubey, A. K.; Pandey, M. D.; Dubey, R. P. (Communications in Mathematics and Applications, 2021)
In this paper, by using the concept of \(α,β\)-admissible mappings with respect to \(Z\)-contraction, we prove some fixed point results in complete metric-like spaces. Our results generalize and extend several well-known results on literature. An example is given to support the obtained results.